2008
DOI: 10.1158/1078-0432.ccr-08-0575
|View full text |Cite
|
Sign up to set email alerts
|

KIT Gene Mutations and Copy Number in Melanoma Subtypes

Abstract: Purpose:We recently identified a KITexon11mutation in an anorectal melanoma of a patient who had an excellent response to treatment with imatinib.To determine the frequency of KIT mutations across melanoma subtypes, we surveyed a large series of tumors. Experimental Design: One hundred eighty-nine melanomas were screened for mutations in KIT exons 11, 13, and 17. KIT copy number was assessed by quantitative PCR. A subset of cases was evaluated for BRAF and NRAS mutations. Immunohistochemistry was done to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

29
493
6
17

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 606 publications
(545 citation statements)
references
References 43 publications
29
493
6
17
Order By: Relevance
“…Discussion c-Kit mutations have recently been identified in certain subsets of melanoma, such as acral, mucosal and skin with sun-induced damage Beadling et al, 2008), but the biological significance of these mutations remains unclear. We have shown here for the first time that c-Kit mutants use a different molecular mechanism than N-Ras or B-Raf oncogenes to transform melanocytes.…”
Section: D576pmentioning
confidence: 99%
See 2 more Smart Citations
“…Discussion c-Kit mutations have recently been identified in certain subsets of melanoma, such as acral, mucosal and skin with sun-induced damage Beadling et al, 2008), but the biological significance of these mutations remains unclear. We have shown here for the first time that c-Kit mutants use a different molecular mechanism than N-Ras or B-Raf oncogenes to transform melanocytes.…”
Section: D576pmentioning
confidence: 99%
“…The presence of a mild hypoxic environment in the skin has already been described (Bedogni et al, 2005), but it remains to be determined whether hypoxia is elevated in the skin located at the extremities of the hands and feet or in the mucosa where acral and mucosal melanoma develop. This strict dependency of c-Kit mutants on the microenvironment could explain the low frequency of c-Kit mutations in cutaneous melanoma (around 2%) Beadling et al, 2008). Interestingly, HIF-1a has also been identified as a target for microphthalmia-associated transcription factor (MITF) (Busca et al, 2005).…”
Section: D576pmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, others confirmed the presence of KIT mutations in the invasive portion of primary malignant melanomas and in their metastatic deposits. [7][8][9] These findings suggested that targeted molecular therapy with tyrosine kinase inhibitors could be successful for melanoma, which is a notoriously difficult malignancy to treat. Indeed, promising results have emerged from clinical studies investigating the use of imatinib for melanoma patients with confirmed KIT-activating mutations.…”
mentioning
confidence: 99%
“…Acral, mucosal, and chronic sun damaged skin melanomas have been shown to harbor KIT mutations while non-chronic sun damaged skin melanomas generally do not since they are often characterized by BRAF or NRAS mutations. [7][8][9]14,15 The frequency of KIT-activating mutations in specific melanoma subtypes is relatively low with reports of 15% for acral, 19% for mucosal, and 17% for chronic sun damaged skin melanomas. 15,16 Ocular melanoma, although a rare melanoma subtype, does account for the majority of all intraocular malignancies.…”
mentioning
confidence: 99%